Semantic ambiguity does not imply syntactic ambiguity - López-Astorga, Miguel (2025)
A problem to solve in generative grammar is to account for why children are able to note when a sentence or expression is ambiguous, even if they have not received explicit training for that. The theory of mental models can give an explanation in that way. That explanation is based upon the idea that people interpret linguistic messages by considering the semantics models corresponding to them, and it has been also proposed that the syntactic structures of those messages can be recovered by taken those very models into account. However, the point of this paper is that it tries to show that ambiguity at semantic level, that is, the cases in which models referring to different facts can be attributed to one sentence, does not necessarily lead to ambiguity at syntactic level. As it is argued, it is possible to capture models describing several opposite circumstances by means of only one logical form.